A rare case of trigeminal neuralgia - Kumari, Monica; Upadhyaya, Vaishali; Ghanghas, Mohit (Indian Journal of Case Reports, 2019)
Trigeminal neuralgia also called Fothergill disease or Prosopalgia is a neuropathic disorder characterized by episodes of intense pain in the face originating from disorders of the trigeminal nerve. Here, we present an unusual case of trigeminal neuralgia due to metastasis from hepatocellular carcinoma in a 76-year old patient. Magnetic Resonance Imaging ofthe brain revealed a mass lesion in the skull base. With suspicion of the mass being metastatic, further imaging and investigations were done, which revealed the presence of hepatocellular carcinoma. This report highlights that metastatic mass lesion can be a cause of trigeminal neuralgia and that hepatocellular carcinoma can have an unusual presentation such as skull base metastasis.